Hubungan Kondisi Ibu dan Berat Badan Lahir Bayi dengan Kejadian Stunting - Calista Hadianti Ratu Pertiwi; Heny Yuniarti; Kamilia Dwi Utami (Pusat Riset dan Inovasi Nasional, 2025)
Research on variables that impact the occurrence of stunting, namely maternal circumstances during pregnancy, which include maternal age, maternal BMI, maternal weight increase throughout pregnancy, and newborn birth weight, remains contentious and has not been thoroughly investigated. The goal of this study was to examine the association between maternal circumstances during pregnancy, child birth weight, and the occurrence of stunting in toddlers at the Bangetayu Health Center in Semarang City. This study utilized an observational analytical case-control approach with a purposeful selection of 80 children (40 stunted and 40 not stunted). The factors investigated were maternal circumstances such as maternal age during pregnancy, maternal weight increase during pregnancy, maternal BMI, infant birth weight, and the prevalence of stunting in toddlers. The data were analyzed using univariate, bivariate, and multivariate methods. This study found a strong correlation (p-value < 0.001) between mother age during pregnancy and stunting rates. However, no significant link was seen between maternal weight growth during pregnancy (p = 0.805). Stunting is associated with maternal BMI (p-value < 0.001). There is no significant link between infant birth weight and the incidence of stunting (p-value = 0.745). Maternal age is the most influential variable on the incidence of stunting at the Bangetayu Health Center, with mothers aged 20-35 years having a 13 times higher risk of giving birth to stunted children and mothers with abnormal BMI having a 9 times higher risk. The frequency of stunting is linked to maternal conditions and newborn birth weight.